Students’ Perspectives on the Role of Artificial Intelligence in Learning and Readiness for the Workforce - Ma’ruf , Muhammad; Ricky Saputra; Irwansyah Suwahyu; Putri Maharani, Geby (Jurnal MediaTIK, 2025)
A concise and the rapid advancement of digitalization and industrial technology has created a high demand for expertise in the field of artificial intelligence (AI). This study aims to explore students’ perceptions of the role of AI in the learning process and their readiness to enter a workforce increasingly driven by technology. Using a quantitative survey of 85 students in Makassar, the findings reveal that although awareness of AI’s benefits is relatively high, practical experience in its application remains limited. Students generally believe that AI can enhance learning efficiency, support data analysis, and better prepare them for future careers. These results highlight the importance of integrating AI into higher education curricula to equip students with analytical, programming, and problem-solving skills that align with the demands of the global labor market.